Case Report: The compound heterozygotes variants in FLT4 causes autosomal recessive hereditary lymphedema in a Chinese family - Xiang, Qinqin; Chen, Jing; Xiao, Xiao; Xu, Bocheng; Xie, Hanbing; Wang, He; Yang, Mei; Liu, Shanling (Frontiers in Genetics, 2023)
Background: Lymphedema is a local form of tissue swelling, which is caused by excessive retention of lymph fluid in interstitial compartment caused by impaired lymphatic drainage damage. Primary lymphedema is caused by developmental lymphatic vascular abnormalities. Most cases are inherited as autosomal dominant, with incomplete penetrance and variable expression. Here we report compound heterozygotes variants in FLT4 of a Chinese family associated with primary lymphedema display autosomal recessive inheritance. Case presentation: Trio-whole-exome sequencing (Trio-WES) was performanced to analyse the underlying genetic cause of a proband with primary lymphedema in a Chinese family. Sanger sequencing was used to validate the variants in proband with primary lymphedema and members of the family with no clinical signs and symptoms.We reported compound heterozygotes for the Fms Related Receptor Tyrosine Kinase 4(FLT4) gene detected in the proband, who carrying two different point variants. One was a missense variant(NM_182925.5;c.1504G>A,p.Glu502Lys), and the other was a recurrent variant(NM_182925.5;c.3323_3325del,p.Phe1108del). The missense variant c.1504G>A was detected in the proband, unaffected father, and unaffected paternal grandmother but not detected in unaffected paternal grandfather. The recurrent variant c.3323_3325del was detected in the proband, unaffected mother, and unaffected maternal grandfather but not detected in unaffected maternal grandmother. Our results suggests the possibility of an autosomal recessive inherited form of primary lymphedema resulting from variants of FLT4 encoding the vascular endothelial growth factor receptor-3. Conclusion: The results of the present study identifed compound heterozygotes FLT4 variants in a family with primary lymphedema which provides more information for autosomal recessive primary lymphedema caused by FLT4.